(untitled) - Cheng, Stephen Shao-Chung (Singapore, 1987)
This book involves discreet signals and events, precisely dictated by appropriate logic funtions. Fundamentally all complex functions are built upon a few elementary simple logic. Solid state circuits perform logic as continuous physical changes, which represent and result in corresponding designated discreet stable logic levels.
Keywords: Digital electronics